Interdisciplinary Drivers of Fiqh Muamalah: Social, Economic, and Technological Perspectives - Zuzanti, Zakia (Sinergi International Journal of Islamic Studies, 2024)
This narrative review investigates the application of fiqh muamalah in contemporary Islamic economic systems, focusing on its integration within social, economic, and technological domains. The objective is to evaluate how various structural and contextual factors influence the implementation of Islamic jurisprudential principles in modern finance. Literature was sourced from Scopus, Google Scholar, JSTOR, and other scholarly databases using thematic keyword searches. Criteria for inclusion prioritized peer-reviewed, empirical, and interdisciplinary research published within the past fifteen years. The results indicate that the success of fiqh muamalah is influenced by educational levels, cultural values, income levels, financial accessibility, and the adoption of fintech solutions. Social factors such as financial literacy and community engagement promote public acceptance, while economic conditions like macroeconomic stability and inclusive financial systems support adoption. Technological innovations such as blockchain and smart contracts offer new opportunities, although their alignment with Shariah principles requires regulatory clarity. Comparative and empirical findings reveal that countries with coherent regulations and community-focused financial literacy programs show higher levels of integration. The discussion emphasizes the urgency of overcoming systemic barriers such as regulatory fragmentation, institutional resistance, and educational limitations. Interdisciplinary Drivers of Fiqh Muamalah: Social, Economic, and Technological Perspectives.